Research on the Application of Acoustic Far Detection Technology in Relief Well - ZHAO Long; LI Zhen; GUO Shangjing; SUN Xiaofang (Cejing jishu)
Once a blowout occurs in the process of oil drilling, the losses are often inestimable. Relief well is an effective technical means to control the accident well, and it needs to accurately detect the location of the accident well in the implementation process. This paper studies the feasibility of acoustic far detection imaging in the location of the accident well. Based on the three-dimensional finite-difference time-domain method, the scattering wave field of the adjacent well excited by the dipole sound source is simulated, and the response characteristics of different types of polarized waves when there are two adjacent wells in different azimuths are analyzed. On this basis, the location of the adjacent well is imaged by using the measured data. The results show that the acoustic far detection imaging can accurately image the adjacent wells in different azimuths in the relief well, which is of great significance for the location of the accident well.